“Para tales amos, tales criados”. La actividad esclavista de una familia de Arequipa durante el siglo XVIII - Calderón Valenzuela, Fernando (Jahrbuch für Geschichte Lateinamerikas, 2019)
This paper explains the importance of both slavery and its commercial trends for domestic economy by analyzing the enslaver practices of an elite family. Statistical analysis is used to explore the role slavery played in the socio-economic development of the Tristán family in the 18th century Arequipa. The Tristán family participated in the retail trade of slaves, among other economic activities.